Comparative Study between Operative and Conservative Management of Penetrating Anterior Abdominal Stab Injuries - Dayem, Ahmad Yahia Abdel; Aiad, George A. N.; Mikhail, Hany M. S.; Elshwadfy, Mohammed; Al Aziz, Ahmad Abd (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Presently, non-operative management of penetrating abdominal stab injuries has been standardized in several trauma centers. This strategy has appromising outcome conserving decreasing morbidity. Aim of the work: This study aimed to assess the safety and feasibility of SNOM of patients having penetrating abdominal stab injuries not indicating emergent laparotomy and to identify a protocol for selection of patient candidates for non-operative management in a tertiary care hospital in Egypt. Patients & Methods: This is a prospective study that involved patients who presented to the casualty department of Kasr Elainy teaching Hospital, in the period from August 2018 to August 2020, for management of a penetrating abdominal Stab injuries. Fully conscious, haemodynimacally stable patients were included. Eligible patients were allocated to either SNOM group or immediate operative management (IOM) group. Results: SNOM group included64 patients and IOM group included 40 patients. The age of the patients ranged from 16 to 49 years with a mean of 33±6.8 years, and the majority were males (99%). SNOM failed in 4/69 patients (5.7%) who required delayed laparotomy for peritonitis (2 cases) and HB drop and haemodynamic instability (2 cases). In IOM group, only 3 cases had therapeutic laparotomies (7.3%). The remaining cases had unnecessary laparotomies (92.7%). Statistically significant higher LOS was seen in SNOM group (p<0.05). However, less unnecessary laparotomies and lower incidences of complications were noted (p<0.01). Conclusion: vital signs together with abdominal examination are the most important clinical criteria in decision making in penetrating abdominal stab injury patients When surgery is not absolutely indicated, SNOM is a safe and feasible approach in management of penetrating abdominal stab injury by following proper management algorithm and selection criteria.